Topics of support among women with infertility problems. - Pung, Wun Chiew; Jariah, Binti Mohd. Jan
Infertility affects about 8% to 12% of couples worldwide (Bushnik, Cook, Yuzpe, Tough, & Collins, 2012). Although it is a global health problem, majority of infertile couples are centered in developing countries (Allahbadia, 2013; Ombelet, 2011), making this an issue of concern because of socio-cultural beliefs that discriminate childless couples and the lack of infertility care in this part of the world. Couples who are childless not only suffer from psychological and emotional effects, but there are also economic and social implications especially in societies where the norm is for children to look after their aged parents. Previous studies on infertility have either focused more on high-income European and American societies (Daniluk & Trench, 2007), or on issues pertaining to infertility treatment ( Bahamondes & Makuch, 2014), clinical, epidemiological and socio-cultural aspects of infertility (Dhont, 2011), and experiences of infertile women (Ceballo, Graham, & Hart, 2015). This study, however, aims to examine infertility in Malaysia, a less researched region of Southeast Asia. It investigated the topics of focus when women with infertility problems give online peer support by employing a content analysis method to analyse six months of messages posted in a Malaysian online forum. The analysis adopted Goldsmith’s (2004) six topics of support and the findings show that topics that emphasize camaraderie among the women are particularly favoured in the forum. However, unlike previous studies of social support, emotions are not given much attention which may be indicative of the high level of sensitivity that the infertility problem poses to women in this region of the world.